The impact of left atrium size on selection of the pulmonary vein isolation method for atrial fibrillation: Cryoballoon or radiofrequency catheter ablation - Ikenouchi, Takashi; Inaba, Osamu; Takamiya, Tomomasa; Inamura, Yukihiro; Sato, Akira; Matsumura, Yutaka; Sato, Hiroyuki; Hirakawa, Akihiro; Takahashi, Yoshihide; Goya, Masahiko; Sasano, Tetsuo; Nitta, Junichi (The American heart journal, 2021)
Pulmonary vein isolation (PVI) is the cornerstone of ablation strategies for atrial fibrillation (AF), and noninferiority of cryoballoon (CB) over radiofrequency (RF) ablation has been previously reported. One of the risk factors of recurrence is left atrium (LA) enlargement. This study aimed to analyze the impact of LA enlargement on the selection of CB or RF ablation for AF patients. A total of 2,224 AF patients (64.4 ± 10.7 years, 65.5% male) who underwent PVI were analyzed retrospectively. Left atrial diameter (LAD) and volume (LAV) were measured using echocardiography before the procedures. LA enlargement was defined as LAD ≥40 mm and LAV index (LAVI) ≥35 mL/m2. Patients undergoing CB and RF ablation were propensity score matched, and 376 matched pairs were evaluated. Cox proportional hazard analysis revealed that LAD (95% CI, 1.01-1.05), LAV (95% CI, 1.01-1.02), and LAVI (95% CI, 1.01-1.03) were independent predictors of recurrence. CB showed equivalent clinical outcomes to those of RF with shorter procedure time required for patients without LA enlargement. CB was inferior to RF in patients with LA enlargement (LAD, 74.5% vs 84.6%, P = .028; LAVI, 74.7% vs 83.4%, P = .015), and large LAVI was associated with a higher prevalence of non-PV foci (35% vs 29%, P = .008). CB ablation may be recommended for patients without enlarged LA based on the short procedure time and efficacy, whereas RF would be more appropriate in large LAs. LAVI may be a valuable reference to predict PVI outcomes and in selecting the ablation method.